Answer:
![p(x) = x^(3) + 3x^(2) -4 = (x-1)(x+2)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/phyey5ip5q8gw49r8iczmkexjt0q6vk3ls.png)
Explanation:
The given polynomial
![p(x) = x^(3) + 3x^(2) -4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/alj68m7sn5dmz3fa2arl3lcm0nugm4tjxp.png)
Now, given that (x-1) is a factor of the above equation.
Now, divide the given polynomial with the factor (x-1)
By Long division, we get
Quotient =
and Remainder = 0
So, by the Remainder theorem
Now, Simplifying the quotient further, we get
=
=
or,
= (x+2)(x+2)
Hence, the given polynomial
can be written as a product of linear factors.
![p(x) = x^(3) + 3x^(2) -4 = (x-1)(x+2)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/phyey5ip5q8gw49r8iczmkexjt0q6vk3ls.png)